Iris Image Quality Testing and Iris Verification - Lidong Wang (Institute of Advanced Engineering and Science, 2013)
The purpose of this study was to investigate the iris image quality and iris verification of eyes in brown, hazel, green, and blue, respectively, and the iris image quality and iris verification under different conditions such as the changed stand-off distances, the motions of the head and eyes, with glasses, and without glasses. A comparative study of three eye colors in brown, hazel, and green was conducted using a non-parametric method based on the H test. The H test results show that there is no significant difference in the iris image quality of eyes in brown, hazel, or green when the level of significance is 0.05.DOI:http://dx.doi.org/10.11591/ijece.v3i4.2769